Analysis of Consumer Perception Regarding the Quality of Services Offered by Casa Ecologica Guesthouse - Loredana Dinu; Gabriel Dinu; Jeanina-Biliana Ciurea (Ovidius University Annals: Economic Sciences Series, 2024)
This paper explores the analysis of consumer perception in the context of services provided by the Casa Ecologica Guesthouse. The study investigates how customers perceive the quality, sustainability, and overall experience offered by this ecologically oriented guesthouse. The obtained results provide a profound understanding of customer expectations and satisfaction, thus offering valuable perspectives for the continuous improvement of services within the ecological hospitality sector.